2018
DOI: 10.1080/02770903.2018.1523930
|View full text |Cite
|
Sign up to set email alerts
|

Ozone pollution and asthma emergency department visits in the Central Valley, California, USA, during June to September of 2015: a time-stratified case-crossover analysis

Abstract: Objective: The San Joaquin Valley (SJV) exceeds the state and national standards for ozone (O3).This study investigates whether short term exposure to O3 is associated with asthma emergency department (ED) visits. Methods: We identified 1101 ED visits in June-September of 2015 in SJV, California, who lived within 15 km of active air monitors. Conditional logistic regression models were used to obtain the odds ratio (OR) and 95% confidence interval (CI) associated with an interquartile (IQR) increase in ozone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Gharibi et al [50] showed that phenolic contents increased in achillea (Achillea pachycephalla) collected from different regions of Iran under water stress, which is in agreement with our results that showed that phenolic contents of C. arenarius and C. ciliaris halophytic species were increased under water stress conditions. Results showed that total phenolics of C. arenarius of the Salt Range remarkably decreased under drought stress (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
“…Gharibi et al [50] showed that phenolic contents increased in achillea (Achillea pachycephalla) collected from different regions of Iran under water stress, which is in agreement with our results that showed that phenolic contents of C. arenarius and C. ciliaris halophytic species were increased under water stress conditions. Results showed that total phenolics of C. arenarius of the Salt Range remarkably decreased under drought stress (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is consistent with prior research associating an increased risk of hospital readmission for pediatric asthma with both indoor air pollution (such as bedroom air quality and tobacco exposure) and traffic-related outdoor air pollution (15,42,43). Our result is also consistent with evidence that ozone concentration had a significantly positive association with asthma exacerbations for children (44,45). This study allows us to conclude that outdoor air pollution (ozone) in neighborhoods where children live and play should be considered a significant risk factor for hospitalization among children with asthma.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have also found positive relationships between PM 2.5 and asthma hospitalization or ED visits for pediatric patients [24][25][26][27]. Moreover, previous research revealed the adverse effects of ozone concentration on asthma exacerbations for children in different settings, such as Texas [28], New York [29], California [30], China [24], HongKong [31] and Korea [32].…”
Section: Discussionmentioning
confidence: 97%